Comparative analysis of the liver‐protective effects of raw and stir‐fried semen of Hovenia dulcis in rats via gas chromatography–mass spectrometry–based serum metabolomic profiling and chemometrics. (17th January 2023) - Lv, Pan; Zhu, Fei; Lv, Meiyan; Bao, Jiaqi; Lv, Linying; Xu, Xiangwei; Tao, Yi
Abstract: In this study, we used a serum metabolomics methodology based on GC coupled with MS (GC–MS) to investigate the liver‐protective effects of raw and stir‐fried semen of Hovenia dulcis in rats models of carbon tetrachloride–induced liver injury. Multivariate statistical analysis, such as principal component analysis and orthogonal partial least squares discriminant analysis, were performed to examine changes in the metabolic state of rats with carbon tetrachloride–induced liver injury, as well as the recovery pattern of rats pretreated with the raw and stir‐fried semen of H. dulcis . Liver tissues were subjected to histopathological examination. A total of 47 biomarkers were predicted to contribute to the dynamic pathological processes in the liver injury, such as phenylalanine, glutamic acid, glycine, arachidonic acid and linoleic acid. Further analysis revealed that pathways associated with phenylalanine, tyrosine and tryptophan biosynthesis, and linoleic acid metabolism were altered in the injured liver, and that pretreatment with raw and stir‐fried semen of H. dulcis abolished the changes in the aforementioned metabolic pathways.